PENGARUH INDEPENDENSI, GENDER, PENGALAMAN AUDITOR, DAN KOMPLEKSITAS TUGAS TERHADAP AUDIT JUDGEMENT PADA KANTOR AKUNTAN PUBLIK DI SURABAYA - Rizky Ryant Pandoyosiwi; Soemaryono Soemaryono (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study examines the influence of auditor independence, gender, auditor experience, and task complexity on audit judgement at Public Accounting Firms (KAP) in Surabaya.. A quantitative approach was adopted, with primary data collected via questionnaires distributed to 85 auditors from 18 active KAPs registered in the IAPI 2025 directory. Purposive sampling was applied with the criteria of minimum D3 education and at least one year of audit experience. Data were analysed using multiple linear regression with SPSS version 23. The findings reveal that auditor independence (sig. 0.039), auditor experience (sig. 0.019), and task complexity (sig. 0.004) each significantly influence audit judgement, while gender (sig. 0.689) does not. Simultaneously, the four variables explain 49.5% of the variation in audit judgement (Adjusted R² = 0.495). These results underscore the importance of maintaining independence and accumulating audit experience as key drivers of professional judgement quality.